Evaluating Public Health Nurses’ Preparedness for Nuclear Disasters in Japan: A Cross-Sectional Study - Yamada, Yumiko; Yamaguchi, Takumi; Matsunari, Yuko (Journal of disaster research, 2025)
This study investigates the preparedness of public health nurses (PHNs) for nuclear disasters in Kagoshima Prefecture, Japan, following the devastating 2011 Great East Japan Earthquake and subsequent Fukushima Daiichi Nuclear Power Station accident. Focusing on PHNs’ roles in community health management during disasters, we assessed nurses’ knowledge and skills in initial response, including the risk assessment of radiation exposure, health education, and evacuation assistance. We also explored demographic factors, educational background, and participation in disaster training. The findings reveal PHNs’ significant lack of confidence in performing essential duties immediately following a nuclear incident, with only 7% answering that they could perform somewhat adequate post-disaster public health activities. Furthermore, the study highlights deficiencies in practical skills, particularly in administering stable iodine tablets and assisting in evacuations, underscoring the need for improved training programs. The results indicate that, even 12 years after the accident, PHNs’ disaster response capabilities, especially in regions with nuclear facilities, must be urgently enhanced with the cultivation of practical skills, and continuity-in-response capabilities must be assured using systematic training and education. This study underlines the critical need for a comprehensive approach to improving health professionals’ preparedness for nuclear emergencies, with implications for both national and international nuclear disaster policy.